DAMPAK WANITA KARIR TERHADAP KELUARGA - Huda, Afiful (USRATUNA: Jurnal Hukum Keluarga Islam, 2019)
Career women are women who have developments and advances in the field of work or position in order to achieve safety and nobleness. Nowadays a lot of women have worked outside the home, and a lot of them have become career women. Women work in law may be based on Islamic law with various conditions. Impacts arising from women (wives) working on the family, namely (1) positive impacts and (2) negative impacts.